2015
DOI: 10.1590/0103-9016-2013-0401
|View full text |Cite
|
Sign up to set email alerts
|

Salinomycin and virginiamycin for lactating cows supplemented on pasture

Abstract: Animals on pasture generally show higher feed efficiency as a result of the use of antibiotics. This study evaluated the effect of the antimicrobials salinomycin and/or virginiamycin on production and the ruminal parameters of supplemented dairy cows grazing on Panicum maximum cv. Tanzania. Twelve Holstein/Zebu multiparous cows were used, distributed in three Latin squares, one for the evaluation of ruminal parameters, and the others for production parameters. Cows on pasture were fed 50 % of their estimated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
(23 reference statements)
1
1
1
Order By: Relevance
“…Our findings are in conflict with those reported by Oliveira et al (2015), who worked with lactating Holstein/Zebu cows by comparing control group, without antimicrobials, with a group receiving salinomycin at the dose of 120 mg kg −1 LW, a group receiving VM at 150 mg kg -1 LW, and a group receiving salinomycin plus VM at 120 and 150 mg kg -1 LW, respectively. The authors concluded that there was no difference in DM digestibility.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings are in conflict with those reported by Oliveira et al (2015), who worked with lactating Holstein/Zebu cows by comparing control group, without antimicrobials, with a group receiving salinomycin at the dose of 120 mg kg −1 LW, a group receiving VM at 150 mg kg -1 LW, and a group receiving salinomycin plus VM at 120 and 150 mg kg -1 LW, respectively. The authors concluded that there was no difference in DM digestibility.…”
Section: Discussioncontrasting
confidence: 99%
“…Disagreeing with our observations, Oliveira et al (2015) worked with Holstein/Zebu cows and did not find differences in EE digestibility including VM or associating VM with salinomycin in the diet as compared with the group with antimicrobial agents.…”
Section: Discussionsupporting
confidence: 68%
“…Goodrich et al (1984) evaluating performance data of approximately 16,000 cattle, reported that animals fed monensin gained more weight and consumed less feed than animals fed control diets. Additionally, Oliveira et al (2015) reported a decrease in 14% on pasture DMI when supplemented lactating cows on pasture received virginiamycin. Rogers et al (1995) conducted a series of studies to evaluate the effects of virginiamycin on performance of feedlot cattle and observed an increase in ADG and feed conversion when animals were fed diets with the additive inclusion.…”
Section: Discussionmentioning
confidence: 99%